ANALISIS USER EXPERIENCE DAN USER INTERFACE (UI/UX) PADA WEBSITE MENGGUNAKAN METODEGOOGLE DESIGN SPRINT - Andryadi, Aan Ansen; Hasri Fatonah, Neng (Jurnal Teknologi dan Bisnis, 2021)
CV Tirta Kalimaya is a company engaged in Water Treatment which has products in two categories, namely Hexabion and Biotech. The marketing technique uses digital marketing, namely market places and websites. The current condition of the website has very few visitors, one of the factors is because the user interface and user experience are not quite right. It is important to pay attention to the user interface and user experience (UI/UX) so that the product can be used properly by users according to its functionality. This study aims to make the CV Tirta Kalimaya company website able to provide what users/website visitors need in terms of functional and visual design by analyzing and designing the user interface and user experience using the Google Design Sprint method, which consists of 5 stages namely, understand, diverge. , decide, prototype and validate. For the validate process using A/B Testing by displaying two variables to see which variable gets good performance. Based on the analysis, implementation and evaluation resulted in a final prototype that has been validated, in terms of appearance, duration of use to consideration of criticism and suggestions from users. And produce user interfaces with matching color schemes, consistent layouts and user experiences that match the respondent's mindset to get information or achieve goals